Double Continuum Model of Evolution of Precursor Droplets in the Flow of Heat Transfer Medium of a Plasma Chemical Reactor; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Zhukov I. S. Ilya (2016, 2016)
Title screen